Deep desulfurization of gasoline by electrochemical oxidation–distillation. (3rd March 2016) - Li, Jing-Jing; Zhou, Fei; Tang, Xiao-Dong; Wang, Fang; Hu, Na
ABSTRACT: An electrochemical oxidation−distillation method with constant current 500 mA was proposed to reduce the sulfur content in gasoline in this work. After electrochemical oxidation−distillation, the sulfur content of gasoline decreased from 514.65 to 10.20 μg/g. On the basis of these experimental results, an oxidation mechanism of electrochemical oxidative desulfurization for gasoline was proposed.